(3GdGSJKeGQaj GdWGbGJ GdeJLOOI (B:s (3GdJhLg, GdSjGSGJ hGdGfLGRGJ aj GdLRGFQ (B/s - (3Hf YGeQ, jMj YeGO GdOjfs ((3GdLRGFQ(B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3GdGSJKeGQ aj GdWGbGJ GdeJLOOI eagheg h GfhGYg h NUGFUg ,OhGaY h GSHGH GdJhLg heJWdHGJ GdWGbGJ GdeJLOOI ,SjGSGJ h Jehjd eTGQjY GdWGbGJ GdeJLOOI h GdJLGQI h GdGSJgdGc aj gPG GdeLGd ,Gdgjcd GdeDSSj h GdGWGQ GdbGfhfj ddWGbGJ GdeJLOOI aj GdLRGFQ h hGbYgG aj GdLRGFQ (B. s
(3GdeQGLY U(B.135-146 s
Keywords: (3GdGSJKeGQs; (3GdehGQO GdeJLOOIs